ANALISIS PENERIMAAN USAHATANI DAN STRATEGI DALAM PENGEMBANGAN AGRIBISNIS JERUK GERGA DI DESA CUGUNG LALANG KECAMATAN UJAN MAS KABUPATEN KEPAHIANG - indah, indah fitria; Fitria, Indah (University of Prof. Dr. Hazairin, SH, 2023)
Indonesia is an agricultural country where most of the population makes a living as farmers. This is because the territory of Indonesia is in the form of an archipelago with a mountainous topography, so it is very suitable for planting various kinds of crops (food, plantations, horticulture, and others). With this consideration, the agricultural sector is very important in creating jobs to generate income for residents living in pedes. Gerga oranges are currently widely marketed in Bengkulu City. Consumers of fresh Gerga oranges can buy in existing traditional markets or directly or to the place of production. However, the distribution of the Gerga orange market in Bengkulu City has not been evenly distributed until now, often consumers cannot buy Gerga oranges because the supply runs out or do not know the places that sell Gerga oranges. The scale of supporters is still small, promotion and a fixed market position for Gerga oranges are not yet available